Increase of the productive level as a demand for the conscious content assimilation of Philosophy: student´s perception - Julio Fragoso Fragoso; Ana María Molina Gómez; Lian Roque Roque; Maritza Cabrera Robau (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2019)
Foundation: University students do not consciously assimilate that the system of knowledge of the discipline Society and Philosophy may help them solving new problems and situations using its concepts and logical operations. Objective: describe the student´s perception about the conscious assimilation of the content of the discipline Society and Philosophy, taught with an increment of the productive level. Methods: pedagogical research realized at the University of Medical Sciences, Cienfuegos, from February to July 2018, in four first year groups of the medical career at their Philosophy lessons. There was an increase of the productive assimilation level in the seminar guidelines and practical lessons, on the bases of designing integrating questions. The number of questions decreased. It was applied a survey to the students to confirm the predominance of the assimilation productive method over the reproductive one in the seminaries may strengthen the conscious assimilation of the subject. The measurement was done at concluding the topic related to Marxist-Leninist nosology since it is considered essential to develop the logical thinking of the future health professional. Results: 95% of the students validated the transformation applied to the guidelines of the practical lessons and seminaries, as a way for a better assimilation of knowledge. They acknowledge the importance of the subject for a better understanding of the world and their future profession. Conclusion: it was demonstrated that the level of productive assimilation in frequent evaluation of the discipline Philosophy and Society the university student assumes consciously that the discipline may help them in the solution to many problems and situations using its concepts and logical operations.